The effect of different production of forage and growing conditions on some biochemical parameters of liver and chemical composition of muscle tissue of juvenile tilapia (Experimental biology, 2018)
The industrial development of fish farms in Kazakhstan is a priority direction in development of agriculture. Growing fish in aquaculture allows to obtain environmentally friendly products at economical expenditure of land and water resources. The main problem in razvedenii fish in aquaculture is the improvement of economic efficiency of fish farming. Significant capital investments, high operating costs, expensive special feed currently doing marginally profitable, and often unprofitable the cultivation of traditional object of fishery – carp. The factors that determine the profitability of fish production is the efficiency of feed use, the share of which in industrial fish farming accounts for more than 50% in the cost structure of products. One of the real directions of increase of economic efficiency of aquaculture is the cultivation of valuable fish species. The successful development of technologies of cultivation of objects such as different kinds of sturgeons and their hybrids, trout, and clarify channel catfish, tilapia will improve the efficiency of fish farms. Among these objects are of considerable interest to tilapia. Fish of the family Cichlidae – tilapia possess valuable biological and economic qualities. Rapid growth, high tolerance to adverse environmental factors, resistance to many diseases make these fish one of the perspective objects of industrial fish farming.
Keywords: fry, tilapia, liver microsomal fraction, malonic, alanine aminotransferase, aspartate aminotransferase, the biochemical composition of the spinal muscles.